Stochastic reconstruction of filament paths in fibre bundles based on two-dimensional input data - Gommer, Frank; Wedgwood, Kyle C.A.; Brown, Louise P. (Elsevier, 2015)
Conventional optical microscopy is an inexpensive technique to analyse fibre bundle micro-structures. Compared to micro-computed tomography, the resolution is higher and larger samples sizes can be analysed. This provides, for example, detailed information of filament spacing which will affect subsequent properties. This paper proposes a probabilistic method to reconstruct paths of individual filaments from a series of two-dimensional micrographs. This allows three-dimensional filament arrangements to be reconstructed and the effects of local arrangements on properties to be quantified. For example, for the small sample analysed in this work, a 15% difference in strength values was found.